Walking as “Criticism on the Move” and a Protest Strategy in Contemporary French Travel Writing: The Case of Alexandre Poussin and Sylvain Tesson - Halia Koo (Studies in 20th & 21st Century Literature, 2020)
“Ambulo ergo sum. I walk, therefore I am,” journalist and travel writer Alexandre Poussin declares by way of introduction to his essay Marche avant ('Walking forward') (2011). Likewise, his colleague Sylvain Tesson, with whom he has covered 5,000 km on foot across the Himalayas, writes in Petit traité sur l’immensité du monde ('Small treatise on the vastness of the world') (2005) that he is a twenty-first-century wanderer, “something between the classic traveller on the lookout for the wonders of the world, and the unattached and completely free nomad.” Walking and hiking certainly stand in the tradition of German Romantic vagrancy, but they are also part of an innovative movement. Indeed, in a society ruled by hyperindustrialization, walking becomes the conscious choice of deliberate slowness in reaction to the exorbitant speed offered by modern means of transportation. By reversing the numbing effects of time-space compression, it becomes an anachronistic and nonconformist activity, as well as a form of social transgression, since it allows a voluntary exile and rebellious withdrawal from civilization. The slowing down of travel (already begun in the second half of the twentieth century) and a renewed enthusiasm for walking have paved the way for a reinvention of the contemporary travel narrative, with various outcomes. For Poussin, slow travel is a powerful learning medium and a tool for understanding the world, since the travelers learn to accept their physical vulnerability and to place themselves in a position of fragility and availability in relation to the Other. As for Tesson, while he claims to embrace the Romantic wanderers’ intellectual legacy, his grueling treks and bucolic escapades into the wilderness help him dissociate himself from an anthropocentric vision of the world and be more ecologically aware, in an act of resistance against the excessive industrialization of society. From his perspective, walking is a form of “criticism on the move,” a way to follow“the tracks of postmodern coureurs de bois” and to experience a return to nature, seen as a place of physical and inner regeneration. While Poussin prefers to travel for humanitarian purposes, organizing pedestrian journeys that emulate a spiritual quest or a secular pilgrimage, slow travel gives Tesson the opportunity to reflect on the exploitation of natural resources, and on the uncertain future of humankind. Éloge de l’énergie vagabonde ('In praise of wandering energy') (2007) relates his trekking journey in the Ust-Yurt, an oil-producing region of Central Asia, the source of energy for industrialized societies. In an actively subversive gesture, he decides to follow this area’s network of oil pipelines “by fair means, without any motorized propulsion” in order to complete the same journey as a drop of gasoline. Paradoxically, walking along these symbols of contemporary society’s technocracy allows him to symbolically restore a lost balance and confirm the necessity for humans to reconnect to their intrinsic animal nature. By triggering the thought process, walking ultimately stimulates a philosophical reflection on the consequences of excessive consumption of energy, contributes to the questioning of environmental issues, and encourages debate on the exploitation of nature and its implications for humankind.
Keywords: travel writing; walking; literature and environment; Alexandre Poussin; Sylvain Tesson